Child Behavior Checklist (CBCL),Youth Self-Report (YSR) and Teacher's Report Form(TRF): an overview of the development of the original and Brazilian versions - Isabel A. Bordin; Marina M. Rocha; Cristiane S. Paula; Maria Cristina T. V. Teixeira; Thomas M. Achenbach; Leslie A. Rescorla; Edwiges F. M. Silvares (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The Achenbach System of Empirically Based Assessment (ASEBA) for school-age children includes three instruments for assessing emotional and/or behavioral problems: Child Behavior Checklist (CBCL), completed by parents, Youth Self-Report (YSR), completed by adolescents and Teacher's Report Form (TRF), completed by teachers. This review article gives detailed information on the development of these forms in the United States and Brazil, describing the main changes to the items, scales and score cut-off points in original versions between 1991 and 2001, as well as the process involved in the translation, back-translation and cultural adaptation of the original questionnaires to develop the current official Brazilian versions of the CBCL, YSR and TRF. The utility of these tools for research and clinical practice is highlighted, mentioning epidemiological studies and evaluation of interventions conducted in Brazil. Researchers' and clinicians' doubts regarding the correct use of the current official Brazilian versions are answered, giving examples of frequently asked questions relevant to the Brazilian context.